Role of Flavonoids in Combating Hyperuricemia - Gorrjanal, Basavaraj; Monika, B. M.; Mythreyi, R.; Muthusamy, Karthikeyan; Murugesan, Karthikeyan; Radhakrishnan, Anjuna; Jagannathan, S.; Elango, Boojhana; Basalingappa, Kanthesh M.; Mathanmohun, Maghimaa (International Multidisciplinary Research Journal, 2023)
Individuals tend to have an increased blood uric acid level at a younger age due to their dietary choices and lifestyle, which can lead to major health concerns such as hyperuricemia, gout, cardiovascular disease, nephropathy, and inflammation. Flavonoids have been proven to have strong inhibitory action against xanthine oxidase and be able to lower serum uric acid levels, levels of adenosine deaminase, gene expressions of renal glucose transporter type 9 (mGLUT9) and uric acid transporter 1 (mURAT1), along with increased expression of organic anion transporters (mOAT1 and mOAT3) and organic cation transporters (mOCT1 and mOCT2). Furthermore, flavonoids enhanced renal function and antioxidant activity in hyperuricemic rats. In hyperuricemic mice, genistein reduced renal fibrosis by inhibiting the JAK2/STAT3 and Wnt/β-catenin signaling pathways. Overall, this review reveals that the flavonoids have substantial anti-hyperuricemia and associated disease potential and may be utilized as natural supplements for the treatment of Uric acid-related illnesses.